LEVANTAMENTO DA PRODUÇÃO DE SISTEMAS CONSTRUTIVOS INOVADORES PARA HABITAÇÃO DE INTERESSE SOCIAL - Lopes, Danielle Scardini; Zanoni, Vanda Alice Garcia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The SiNAT-National Technical Evaluation System, created under the PBQP-H - Brazilian Program of Quality and Productivity in Habitat of the Ministry of Cities, acts as the responsible entity for the technical evaluation of products and construction systems performance that do not have a specific Brazilian technical standard. In order to expand the range of technological alternatives for social housing construction in the country, SiNAT allows systems that are not yet standardized (known as innovative systems) to be applied in a large scale since provided with a Technical Assessment Document - DATec, based on Guidelines of performance evaluation. These so-called innovative systems, for the most part, have a high level of industrialization and, consequently, are characterized by rationalization, generating cost reduction, increased work speed, reduced waste and increased sustainability. Despite all these alleged advantages, innovative systems are still not being applied on a large scale within Brazilian territory. In this context, the present research proposes to reflect on the challenges and barriers related to the adoption of large-scale innovative construction systems in Brazil. Through the analysis of data provided by Caixa Econômica Federal, it was possible to identify the main barriers related to the adoption of these systems in the country.